Nest site selection of the Kelp gull (Larus dominicanus) in the Beagle Channel, Tierra del Fuego, Argentina - Suarez, Nicolas Marcelo; Pozzi, Luciana Melina; Yorio, Pablo Martin (Polar Biology)
Nest site selection of Kelp gulls Larus dominicanus breeding in Conejo and Bridges islands, Tierra del Fuego, Argentina, was assessed between 14 and 30 December 2005 to describe variability in nest site features and determine variables affecting nest choice. Fourteen microhabitat variables were quantified at 40 nest sites and at 40 random points in each island during the late incubation stage. Nests at the two colonies were placed on different kinds of substrates across areas with varying degrees of cover provided either by rocks or vegetation. Despite the variability observed in nest site features, rock cover and rocky substrates were the main factors determining nest site selection. At Conejo Island, nest sites presented more rock cover, less percentage of vegetation cover and of vegetation debris substrate, and were placed further from the nearest vegetation in comparison to random points. Similarly, gulls at Bridges Island selected nest sites with more rock cover which were placed mainly on rocky and vegetation substrates. This contrasts with results previously obtained in Argentina, which indicated that vegetation is a key factor influencing Kelp gull nest site selection. Over 80% of the nests at both study colonies were placed on the northern slopes of the islands, relatively more protected from the strong prevailing southwest winds, and nests at both colonies tended to be more protected on their southern side either by rocks or vegetation. Results obtained at Tierra del Fuego confirm the plasticity of microhabitat use by Kelp gulls, and their ability to take advantage of nesting sites according to availability and local environmental factors. Fil: Suarez, Nicolas Marcelo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Pozzi, Luciana Melina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Yorio, Pablo Martin. Wildlife Conservation Society; Estados Unidos. Consejo Nacional de Investigaciones ...